2015
DOI: 10.1016/j.celrep.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes Control Food Intake by Inhibiting AGRP Neuron Activity via Adenosine A1 Receptors

Abstract: It is well recognized that feeding behavior in mammals is orchestrated by neurons within the medial basal hypothalamus. However, it remains unclear whether food intake is also under the control of glial cells. Here, we combine chemical genetics, cell-type-specific electrophysiology, pharmacology, and feeding assays to show that stimulation of astrocytes within the medial basal hypothalamus reduces both basal- and ghrelin-evoked food intake. This occurs by a mechanism of adenosine-mediated inactivation of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
199
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(214 citation statements)
references
References 50 publications
8
199
1
6
Order By: Relevance
“…10A). In addition, we infused ghrelin as a positive control because intra-Arc injection of ghrelin significantly increases food intake during the light period (Yang et al, 2015). We confirmed that intra-Arc injection of 0.7 mM ghrelin increased food intake (86 Ϯ 42 mg for vehicle control, 396 Ϯ 37 mg for ghrelin, p Ͻ 0.0001; Fig.…”
Section: Are P2x4 Receptors Involved In the Control Of Feeding?supporting
confidence: 67%
See 1 more Smart Citation
“…10A). In addition, we infused ghrelin as a positive control because intra-Arc injection of ghrelin significantly increases food intake during the light period (Yang et al, 2015). We confirmed that intra-Arc injection of 0.7 mM ghrelin increased food intake (86 Ϯ 42 mg for vehicle control, 396 Ϯ 37 mg for ghrelin, p Ͻ 0.0001; Fig.…”
Section: Are P2x4 Receptors Involved In the Control Of Feeding?supporting
confidence: 67%
“…We used procedures based on published work (Wong et al, 2015;Yang et al, 2015). Mice (8-to 10-week old; male) were anesthetized with isoflurane (induction at 5%, maintenance at 1%-2.5% v/v) and placed on a stereotaxic apparatus.…”
Section: Methodsmentioning
confidence: 99%
“…Leptin signaling in astrocytes was also recently shown to play an active role in the hypothalamic control of feeding . Recently, astrocytes were shown to control food intake by inhibiting AgRP neuron activity (Yang et al 2015), which suggests astrocytes are indirectly able to promote fertility as restraining AgRP neurons would presumably facilitate GNRH drive, as mentioned previously. Furthermore, Sandau and coworkers demonstrated that the synaptic cell adhesion molecule, SynCAM1, mediates astrocyte-to-GNRH neuron adhesiveness in the mouse hypothalamus (Sandau et al 2011b), and it was shown that astrocyte-to-GNRH neuron adhesiveness via SynCAM1 is important in the control of female sexual development.…”
Section: Astroglial Cellsmentioning
confidence: 60%
“…All the experiments were performed in the early light period with brain slices prepared at 09:00. Acute brain slices that include hypothalamic ARC and VMH were prepared as described in our previous work (Yang et al, , 2015. Briefly, mice were deeply anesthetized with isoflurane and decapitated.…”
Section: Methodsmentioning
confidence: 99%